A new approach to rapid determination of 18 bioactive constituents in Alpinia oxyphylla using UPLC-MS/MS with positive–negative conversion multiple reaction monitor (+/−MRM) technology. Issue 15 (5th April 2016) - Hou, Lei; Zuo, Lihua; Sun, Zhi; Sun, Zhiyong; Zhu, Zhenfeng; Kang, Jian; Gao, Li; Zhang, Xiaojian; Huang, Wenhua
Abstract : A new approach was developed for the simultaneous separation and determination of 18 active components (including one new component) in Fructus Alpinia oxyphylla by UPLC-MS/MS with +/−MRM technology. Abstract : A new approach was developed for the simultaneous separation and determination of 18 active components (including one new component) in traditional Chinese medicines, Fructus Alpinia oxyphylla, by ultra high-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) with positive–negative conversion multiple reaction monitor (+/−MRM) technology. The chromatographic separation was performed on a Waters ACQUITY UPLC® HSS C18 column (2.1 mm × 50 mm, 1.8 μm) with gradient elution using 0.1% formic acid aqueous solution (A) and acetonitrile (B) at a flow rate of 0.3 mL min −1 . This is the first report of the simultaneous determination of 18 bioactive constituents in Alpinia oxyphylla extract by UPLC-MS/MS. Good linear behaviors over the investigated concentration ranges were observed with the values of r higher than 0.998 for all the analytes. The method was reproducible with intra-and inter-day variation less than 3.0% and the recovery of the assay was in the range of 95.5% to 104.6%. The validated method was successfully applied for the analysis of 18 bioactive compounds in Fructus Alpinia oxyphylla extract from different sources and the analysis results were classified by hierarchical cluster analysis (HCA). This study provides a powerful and practical guidance to be used for the comprehensive quality control of Alpinia oxyphylla and lays the foundation for further research of Alpinia oxyphylla .